The Role of Digital Marketing Strategy in Influencing Generation Z Purchasing Decisions on E-Commerce Platforms - Miftachul Ulum; Abdul Mun’im; Maula Safitri (Rashid : Journal of Economic, 2026)
The development of digital technology has transformed consumer behavior, particularly in seeking information and making purchasing decisions on e-commerce platforms. This study aims to analyze the role of digital marketing strategies in influencing Generation Z’s purchasing decisions through a literature review approach. The findings show that content marketing, affiliate marketing, influencer marketing, electronic word of mouth (e-WOM), online customer reviews, and promotional activities contribute to purchasing decisions. In addition, product quality, consumer satisfaction, brand awareness, and pricing strengthen consumers’ purchasing intentions. Consumer trust is identified as a key factor linking digital marketing strategies to purchasing decisions. Therefore, effective and consumer-oriented digital marketing strategies play an important role in encouraging Generation Z’s purchasing decisions on e-commerce platforms..